P732 Impact of different types of physical activity in inflammatory bowel disease. (30th January 2023) - Gofflot, A; Monin, L; Seidel, L; Reenaers, C; Kropp, S; Van Kemseke, C; Latour, P; Forthomme, B; Croisier, J L; Louis, E; Vieujean, S
Abstract: Background: Moderate physical activity (PA) appears to be beneficial for inflammatory bowel disease (IBD), improving the symptoms of the disease and promoting the maintenance of remission. However, little is known about the impact of different types of PA on IBD activity. Methods: IBD patients with stable treatment without steroids for 4 months were prospectively included and randomized into 3 groups: muscle strengthening exercises, aerobic exercises, and a control group. The impact of a 10-week training period with 2 sessions per week was evaluated. Following parameters were collected: clinical activity of the disease (Mayo score for ulcerative colitis or UC, Harvey-Bradshaw index or HBI for Crohn's disease or CD, patient reported outcome or PRO for both), Godin Leisure Time Exercise Questionnaire or GLTEQ (assessing PA level), Metabolic Equivalent Task or MET (assessing sedentarity level), barriers to PA, quality of life assessment (by EuroQol 5 dimensions or EQ5D and Short health scale or SHS), Inflammatory Bowel Disease Fatigue (IBD-F), physical abilities according to exercise stress test and maximum strength test. Results: Between January 2021 and September 2022, a total 33 patients were enrolled in the program. Of these, 24 patients (13 women, 17 CD, median age of 31.6 [IQR, 29.4- 46.4]) completed the program and were included in the analysis (dropout rate of 18.2%). Table 1 shows the characteristics of these patients at inclusion. Eight, six and ten patients were respectively randomized in the muscle strengthening, aerobic exercise and control groups. After the training period, 50% of patients in the muscle strengthening group and 66.7% of patients in the aerobic exercise group showed a clinical improvement (according Mayo score and HBI). Strengthening was associated with significant reduction in PRO rectal bleeding in UC patients (p<0.0001) and aerobic exercise was associated with a significant lowering of HBI (p=0.039). Among the 24 patients, 2 CD patients relapsed in the muscle strengthening group during the training period. Aerobic exercise significantly reduced the barriers to PA (p=0.037). In neither group did we find any positive or negative impact of PA on quality of life or fatigue. Strengthening exercise and aerobic exercise significantly improved VO2max (maximal oxygen consumption) and Pmax in the exercise stress test, respectively. Most of the maximum strength tests were improved in the muscle strengthening group. Conclusion: PA was well tolerated and associated with an improvement of disease activity in the majority of the IBD patients. There may be a variable impact of different types of PA in CD and UC, which should be explored further in larger cohorts.